2014
DOI: 10.1111/cei.12246
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis: a prospective pharmacokinetics and clinical study

Abstract: SummaryAnti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) treatment strategy is based on immunosuppressive agents. Little information is available concerning mycophenolic acid (MPA) and the area under the curve (AUC) in patients treated for AAV. We evaluated the variations in pharmacokinetics for MPA in patients with AAV and the relationship between MPA-AUC and markers of the disease. MPA blood concentrations were measured through the enzyme-multiplied immunotechnique (C0, C30, C1, C2, C3, C4, C6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
1
14
1
Order By: Relevance
“…21 In antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), it was shown that MPA AUC 0-12 correlates with disease activity even if MMF was not recommended as a standard treatment in AAV. 14 Finally, a large inter-individual variability in MPA plasma exposure was documented in these three conditions. 14,29,30 In the present study, SSc patients exhibited a median MPA AUC 0-12 of 44 mg/L.h (interquartile range (IQR) 32–58), close to the targeted range in renal transplant recipients and to the median MPA AUC 0-12 previously reported in SLE and vasculitis cohort.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…21 In antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), it was shown that MPA AUC 0-12 correlates with disease activity even if MMF was not recommended as a standard treatment in AAV. 14 Finally, a large inter-individual variability in MPA plasma exposure was documented in these three conditions. 14,29,30 In the present study, SSc patients exhibited a median MPA AUC 0-12 of 44 mg/L.h (interquartile range (IQR) 32–58), close to the targeted range in renal transplant recipients and to the median MPA AUC 0-12 previously reported in SLE and vasculitis cohort.…”
Section: Discussionmentioning
confidence: 85%
“…20,21 Overall, practitioners generally consider that the target MPA AUC 0–12 range (30–60 mg/L.h) should be the same in autoimmune diseases as in renal transplant recipients. 14 However, to our knowledge, no data are available in SSc patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We did not perform therapeutic drug monitoring of MMF, and the therapeutic doses are, therefore, not known. Previous studies have shown that patients with ANCAassociated vasculitis as well as healthy individuals exhibit a high interindividual variability with respect to the plasma concentrations of MPA, the active metabolite of MMF (15). It was demonstrated that MPA concentrations were associated with outcome in ANCA-associated vasculitis, and possibly, higher dosages of MMF might have resulted in better outcome (16).…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare the relative drug exposure in patients prescribed different doses of MMF, we constructed the variable MPA_AUC 3g corresponding to a daily intake of 3 g MMF. This estimate was made by multiplying MPA_AUC 0–12 by 3 or 1.5, respectively, in patients using MMF at a dose of 1 or 2 g daily [ 26 , 27 ]. Descriptive data were presented using mean ± (SD) or median (IQR or range), and comparative analyses were done using non-parametric statistics including Spearman’s rank correlation ( r s ) coefficient, Kruskal-Wallis test and the Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%